1976
DOI: 10.1128/iai.14.4.1052-1064.1976
|View full text |Cite
|
Sign up to set email alerts
|

Infection cycle of Rickettsia rickettsii in chicken embryo and L-929 cells in culture

Abstract: The infection cycle of Rickettsia rickettsii, studied in slide chamber cultures of chicken embryo and L-929 cells, was found to be complex and did not conform to a one-step growth cycle. Initial uptake kinetics resembled those established for Rickettsia prowazekii, but subsequent events showed very marked differences. Intracytoplasmic growth commenced exponentially without measurable lag. However, very soon after infection, intracytoplasmic rickettsiae began to escape from the host cell into the medium in larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
28
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 14 publications
6
28
0
Order By: Relevance
“…At this ratio approximately 14 rickettsiae were associated with each L cell after 30 min. This was similar to previous reports that the association of R. tsutsugamushi (5), R. rickettsii (24), and R. prowazeki (27) varied directly with MOL.…”
Section: Association Of Rickettsiae With L Cellssupporting
confidence: 91%
“…At this ratio approximately 14 rickettsiae were associated with each L cell after 30 min. This was similar to previous reports that the association of R. tsutsugamushi (5), R. rickettsii (24), and R. prowazeki (27) varied directly with MOL.…”
Section: Association Of Rickettsiae With L Cellssupporting
confidence: 91%
“…Because the endothelial cell is the putative target cell in human infections, our studies over the past several years have focused on the interaction of R. rickettsii with endothelial cells. The kinetics of infection of endothelial cells in culture (10) parallel that shown by Wisseman et al (20) for chicken embryo fibroblasts and mouse L cells. Typically, following internalization by uptake and subsequent escape from the phagosome into the cytoplasm (17,18), the microorganisms replicate by binary fission and rapidly spread to adjacent host cells in the culture.…”
supporting
confidence: 76%
“…Typically, following internalization by uptake and subsequent escape from the phagosome into the cytoplasm (17,18), the microorganisms replicate by binary fission and rapidly spread to adjacent host cells in the culture. In a small percentage of infected host cells, the bacteria also enter the nucleus, a characteristic common to members of the spotted fever group rickettsiae (20).…”
mentioning
confidence: 99%
“…Cohn et al (I) first showed that the entrance of Rickettsia tsutsugamushi into cultured mouse MB III lymphoblasts requires active participation of both the rickettsiae and the host, and a similar result was reported by Walker and Winkler (10) in the R. protoazekiimouse fibroblast (L cell) system. Wisseman et al (13) indicated rapid, bidirectional traffic of R. rickettsii directly across the host cell membrane. However Wisse-251 man and Waddel (14) suggested another mode of entry of R. protoazekii into cultured chicken embryo cells; that is, by phagocytosis into the phagosome and escape from the phagosome into the cell cytoplasm.…”
mentioning
confidence: 99%